2006
DOI: 10.1007/s10529-006-9196-2
|View full text |Cite
|
Sign up to set email alerts
|

Catabolic pathways and biotechnological applications of microbial caffeine degradation

Abstract: Catabolism of caffeine (1,3,7-trimethylxanthine) in microorganisms commences via two possible mechanisms: demethylation and oxidation. Through the demethylation route, the major metabolite formed in fungi is theophylline (1,3-dimethylxanthine), whereas theobromine (3,7-dimethylxanthine) is the major metabolite in bacteria. In certain bacterial species, caffeine has also been oxidized directly to trimethyl uric acid in a single step. The conversion of caffeine to its metabolites is primarily brought about by N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 45 publications
3
92
0
2
Order By: Relevance
“…Paraxanthine and theobromine are further N-demethylated to 7-methylxanthine and xanthine. Xanthine is subsequently oxidized to uric acid by xanthine oxidase/dehydrogenase, and the uric acid enters the normal purine catabolic pathway to form CO 2 and NH z 4 (Dash & Gummadi, 2006). Theophylline, the major caffeine metabolite in filamentous fungi (Hakil et al, 1998), has not been reported as a bacterial metabolite of caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Paraxanthine and theobromine are further N-demethylated to 7-methylxanthine and xanthine. Xanthine is subsequently oxidized to uric acid by xanthine oxidase/dehydrogenase, and the uric acid enters the normal purine catabolic pathway to form CO 2 and NH z 4 (Dash & Gummadi, 2006). Theophylline, the major caffeine metabolite in filamentous fungi (Hakil et al, 1998), has not been reported as a bacterial metabolite of caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is also a major human dietary ingredient that can be found in common beverages and food products, such as coffee, tea, and chocolates. In pharmaceuticals, caffeine is used generally as a cardiac, neurological, and respiratory stimulant, as well as a diuretic (3). Hence, caffeine and related methylxanthines enter soil and water easily through decomposed plant materials and other means, such as effluents from coffee-and tea-processing facilities.…”
mentioning
confidence: 99%
“…Hence, caffeine and related methylxanthines enter soil and water easily through decomposed plant materials and other means, such as effluents from coffee-and tea-processing facilities. Therefore, it is not surprising that microorganisms capable of degrading caffeine have been isolated from various natural environments, with or without enrichment procedures (3,10). Bacteria use oxidative and N-demethylating pathways for catabolism of caffeine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other members of the microbial community may be reduced in abundance whether that be they are outcompeted (i.e., caffeine serves as food source for other species) or sensitive (i.e., caffeine acts as an antimicrobial). It has been reported in earlier studies that caffeine at a relatively low concentration was antimicrobial and resulted in inhibition of growth and death of bacterial strains like E. coli and other bacterial strains particularly upon addition of caffeine at log phase of growth (Dash and Gummadi 2006;Gummadi et al 2012). Indeed, Ramanavièienë et al (2002) found that the growth of E. coli was inhibited significantly at caffeine concentrations as low as 1 g/L.…”
Section: The Impact Of Caffeine On Microbial Communitymentioning
confidence: 97%